Formulation and Sunscreen Activity Assay of Fig Fruit (Ficus carica L.) Extract Cream - Kurniawati, Endah; Firdausia, Rizqa Salsabila; Sari, Kurnia Rahayu Purnomo (MEDIA ILMU KESEHATAN, 2025)
Background: Ultraviolet radiation can cause skin damage and increase the cancer risk. Sunscreen provides skin protection against UV. Cream is one of the popular sunscreen dosage form. The increasing demand of natural resources such as fig fruit is caused by its potential ability as sunscreen.Objective: The aim of this study is to evaluate the sunscreen ability of fig fruit extract and to evaluate the impact of extract concentration variation towards cream physical properties.Methods: Sunscreen activity of extracts were determined by SPF value and IC50. The sunscreen formulation consist of three variation of extract concentration (10%, 15%, 20%). Cream were measured for the SPF value and the physical properties. Results: Fig fruit extract (12500 ppm) had the SPF value namely 29,64 and IC50 value of 948,69 ppm. The SPF value of cream with 10% ; 15% ; 20% concentration respectively were 2,1 ; 5,25 ; 7,74. All cream formulation had good physical properties. Cream F3 had the best stability after 1 month storage. Conclusion: Significant correlation was found between SPF value and concentration of extract in cream. But no significant correlation was found between concentration of extract and physical properties of cream